THE ROLE OF MARKETING IN THE DEVELOPMENT OF SMALL AND MEDIUM-SIZED BUSINESSES IN UZBEKISTAN - Saipullaev Ilhomjon Abdurakhmonovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
This article highlights the importance of Marketing, which is necessary for the development of small and medium-sized businesses. An analysis of the correct implementation of marketing, which is one of the important factors in creating an internal environment, has been carried out. The entire life cycle of the company is divided into 6 periods, and in each period several directions of the main marketing activities are mentioned.